MOTIVATION DEFINITION AND GENERAL CHATACTERIZATION - Drawsheh, Ahlam (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
Poorly motivated children are at risk for disturbances and delays in their socio-emotional and scholastic functioning. This paper examines the motivation and its components, in order to understand better the factors and tools to improve children motivation.